Formation of the target professional Competences of CLIL Teachers - Gulnar Karipbayeva4, Gulnara Azhibekova5, Tanat Ayapova1, Dana Shayakhmetova2, Ainagul Tautenbayeva3, (Opción, 2019)
This article is devoted to CLIL (Subject and LanguageIntegrated Learning) – describes teaching methods, where subjects aretaught in foreign languages via comparative qualitative researchmethods. As a result, assessment in CLIL remains one of the aspectsthat poses difficulties as it depends on the national or local policy andestablished practices to a great extent, and causes intense discussionseven within the CLIL community itself. In conclusion, teachers stilllack competences in preparing/designing teaching materials for theCLIL class, the skills only acquired through long practice.